REKONSTRUKSI INKLUSI SOSIAL DAN KEADILAN GENDER PADA KELUARGA MUDA RENTAN EKONOMI: TINJAUAN PPKN TERHADAP KRISIS PERAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK - Chandra Fhutu Neva; Nurur Risky Aulia; Andry Anshari; Raysyah Putri Sitanggang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of the parental role crisis in character building is a crucial issue for young families facing economic vulnerability. This research is driven by structural challenges within the child protection system that have not effectively reached the grassroots level. The study aims to formulate a family inclusion model based on